Analisis Citra Digital CT Scan Dengan Metode Ekualisasi Histogram dan Statistik Orde Pertama - Dwi Nurhayati, Oky (Jurnal Sistem Komputer, 2015)
this research aims to develop the science and technology of medical image processing CT Scan, which yield an identification system software. Histogram equalization method is the first step in image pre-processing that is applied to the digital images of CT Scan. The next step is statistical texture analysis method of first order to extract the parameters such as mean, variance, standard deviation.the result showed that the histogram equalization method and the statistical texture analysis can be used to distinguish normal CT Scan and abnormal that detected stroke.